Civil Engineering and Symmetry - Antuchevi?ien?, Jurgita (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
A topic of utmost importance in civil engineering is finding optimal solutions throughout the life cycle of buildings and infrastructural objects, including their design, manufacturing, use, and maintenance. Operational research, management science, and optimization methods provide a consistent and applicable groundwork for engineering decision-making. These topics have received the interest of researchers and, after a rigorous peer-review process, eight papers have been published in this Special Issue. The articles in this Printed Edition demonstrate how solutions in civil engineering, which bring economic, social, and environmental benefits, are obtained through a variety of methodologies and tools. Usually, decision-makers need to take into account not just a single criterion, but several different criteria and, therefore, multi-criteria decision-making (MCDM) approaches have been suggested for application in five of the published papers; the rest of the papers apply other research methods. Most approaches suggested decision models under uncertainty, proposing hybrid MCDM methods in combination with fuzzy or rough set theory, as well as D-numbers. The application areas of the proposed MCDM techniques mainly cover production/manufacturing engineering, logistics and transportation, and construction engineering and management. We hope that a summary of the Special Issue as provided here will encourage a detailed analysis of the papers included in the Printed Edition.<false,>